2021
DOI: 10.1002/vms3.693
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory activity of arctigenin against PCV2 infection in a mouse model

Abstract: Arctigenin (ACT) is a novel anti-inflammatory lignan extracted from Arctium lappa L, a herb commonly used in traditional Chinese herbal medicine. In this study, we investigated the molecular mechanism whereby ACT inhibits PCV2 infection-induced proinflammatory cytokine production in vitro and in vivo. We observed that in PCV2 infection+ACT treated PK-15 cells, proinflammatory cytokine production was significantly reduced, compared to the PCV2-infected cells. The transfection and luciferase reporter assay confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In line with a previous study by Sun et al [19], conventional drug-based therapies have led to certain side effects whereas traditional Chinese medicine (TCM) could ameliorate PCV2 infection in animal models [20]. Therefore, this model, could be used to study the mechanism of PCV2 infection as well as to evaluate the antiviral activities of Chinese herbal formulations.…”
Section: Discussionsupporting
confidence: 64%
“…In line with a previous study by Sun et al [19], conventional drug-based therapies have led to certain side effects whereas traditional Chinese medicine (TCM) could ameliorate PCV2 infection in animal models [20]. Therefore, this model, could be used to study the mechanism of PCV2 infection as well as to evaluate the antiviral activities of Chinese herbal formulations.…”
Section: Discussionsupporting
confidence: 64%
“…Arctigenin 4 is a lignan purified from A. lappa seeds which exerted anti-inflammatory activity by suppressing the PI3K/AKT pathway and polarizing M1 macrophages to M2-like macrophages [93]. In another study, arctigenin 4 showed anti-inflammatory effects by suppressing a Porcine circovirus type 2 (PCV2) infection that induced the production of proinflammatory cytokines by inhibiting the phosphorylation and nuclear translocation of NF-κB [94]. Arctigenin 4 also exhibited anti-inflammatory effects in a mouse model of colitis via suppressing MAPK and NF-κB pathways [95].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%